Embryo editing: a proposito di una recente autorizzazione dell’HFEA (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
Taking as a starting point a recent HFEA’s authorization, the article focuses on the international debate stirred by the news on the application of CRISPR-Cas9 to human embryos. The legislative landscape on the permissibility of inheritable genetic modification will be explored, with particular attention to the Italian situation.
Keywords: Embryo editing; CRISPR-Cas9; Embryo experimentation; HFEA; Inheritable genetic modifications